2019
DOI: 10.3390/app9152948
|View full text |Cite
|
Sign up to set email alerts
|

Form-Finding Analysis of a Class 2 Tensegrity Robot

Abstract: In this paper, a new form-finding analysis methodology for a class 2 tensegrity robot is proposed. The methodology consists of two steps: first, the analysis of the possible geometric configurations of the robot is carried out through the results of the kinematic position analysis; and, second, from the static analysis, the equilibrium positions of the robot are found, which represents its workspace. Both kinematics and static analysis are resolved in a closed-form using basic tools of linear algebra instead o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…For the form-finding analysis of the proposed class 2 tensegrity robot, the methodology presented in [20] is applied, where the set of all possible geometric configurations of the robot provided by θ 1 and θ 2 are analyzed, and a subset of equilibrium configurations provided by θ e1 and θ e2 is determined.…”
Section: Form-finding Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…For the form-finding analysis of the proposed class 2 tensegrity robot, the methodology presented in [20] is applied, where the set of all possible geometric configurations of the robot provided by θ 1 and θ 2 are analyzed, and a subset of equilibrium configurations provided by θ e1 and θ e2 is determined.…”
Section: Form-finding Analysismentioning
confidence: 99%
“…For the class 2 tensegrity robot reported in [13] and illustrated in Figure 1, C.G. Manríquez-Padilla et al [20] proposed a solution strategy for the form-finding analysis based on a combination of the fundamental principles of statics and the direct and inverse kinematic position analysis using the geometric parameters proposed by Denavit-Hartenberg [21]. In the same study, a case was presented wherein 14,641 geometric configurations were analyzed, and only 215 were classified as equilibrium geometric configurations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, the authors of the present work have found a picture from 1921 (Figure 1) where Karl Ioganson's tensegrity prototypes can be seen with the first example of a Simplex [2,3], which was patented some decades later. Tensegrity governs the behavior of many structures within the engineering scope [4]. Throughout the years, many definitions have been given to this principle.…”
Section: Introductionmentioning
confidence: 99%
“…If the measurement of these extensions is not available, static modeling is considered. Several methods have been proposed in the literature to determine the equilibrium configurations of tensegrity mechanisms [8,15]. Static workspace computation, using a continuous approach, has been proposed by [2] for a 2-DoF tensegrity mechanism.…”
Section: Introductionmentioning
confidence: 99%